Non-Tariff Measures on Indonesian Tea Products: Do SPS and TBT Impede or Promote the Export? - Putro, Fikri Aldi Dwi; Widyastutik, Widyastutik; Hidayat, Nia Kurniawati (UI Scholars Hub, 2025)
Previous studies highlight the heterogeneous effects of Non-Tariff Measures (NTMs) on international trade. This study identifies the enforcement of NTMs and examines the effects on the export performance of Indonesian tea products. This study employed an inventory (coverage ratio) approach and panel regression with the Poisson-Pseudo Maximum Likelihood (PPML) method. The results indicate that 31 out of 36 analyzed destination countries enforce NTMs, with Vietnam imposing the most prevalent ones. Furthermore, SPS measures substantially promote the export of Indonesian tea products, whereas TBT measures show no significant effect. Therefore, the government needs to provide incentives and harmonize the national Voluntary Sustainability Standards (VSS) scheme and other national standards to comply with NTMs imposed by destination countries.